Omeprazole Treatment Failure in Gastroesophageal Reflux Disease and Genetic Variation at the CYP2C Locus - Kee, Ping Siu; Maggo, Simran D. S.; Kennedy, Martin A.; Barclay, Murray L.; Miller, Allison L.; Lehnert, Klaus; Curtis, Maurice A.; Faull, Richard L. M.; Parker, Remai; Chin, Paul K. L. (Frontiers in Genetics, 2022)
Omeprazole is extensively used to manage gastroesophageal reflux disease (GERD). It is primarily metabolized by CYP2C19. The CYP2C19*17 (rs12248560) allele and the recently described CYP2C:TG haplotype (rs11188059 and rs2860840) are associated with increased enzymatic activity, and may reduce omeprazole exposure. This observational study aimed to investigate the association between these genetic variants and omeprazole treatment failure in GERD. We recruited predominantly New Zealand European GERD patients who either did not respond to omeprazole or experienced breakthrough heartburn symptoms despite at least eight weeks of omeprazole (≥ 40 mg/day). The GerdQ score was used to gauge symptomatic severity. A total of 55 cases were recruited with a median age (range) of 56 years (19-82) and GerdQ score of 11 (5-17). Of these, 19 (34.5%) were CYP2C19*17 heterozygotes and two (3.6%) were CYP2C19*17 homozygotes. A total of 30 (27.3%) CYP2C:TG haplotypes was identified in our cohort, with seven (12.7%) CYP2C:TG homozygotes, and 16 (29%) CYP2C:TG heterozygotes. No significant differences were observed for overall CYP2C19*17 alleles, CYP2C19*17/*17, overall CYP2C:TG haplotypes, and CYP2C:TG heterozygotes (p > 0.05 for all comparisons). Gastroscopy and 24-hour esophageal pH/impedance tests demonstrated objective evidence of GERD in a subgroup of 39 (70.9%) cases, in which the CYP2C:TG/TG were significantly enriched (p=0.03) when compared with the haplotype frequencies in a predominantly (91%) New Zealand European reference population, but not the CYP2C19*17/*17 (p>0.99), when compared with the allele frequencies for the non-Finnish European subset of gnomAD. We conclude that omeprazole treatment failure in GERD is associated with CYP2C:TG/TG, but not CYP2C19*17.